PENGEMBANGAN KREATIVITAS USAHA KAFÃ‰ TENDA DAN WARUNG LESEHAN MELALUI PELAYANAN PRIMA SEBAGAI UPAYA BERWIRASWASTA UNTUK MENGATASI PENGANGGURAN DI KOTA MALANG - Ardani, Tristiadi Ardi (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2005)
One of phenomenon that can be seen in Malang town, especially in the night, through the Veteran Street, we see many tent cafÃ© and lesehan stalls. The same thing we meet also in Sunday morning around Gajayana Stadium. The good management will have significant impact to the income of merchants. However, tent cafes and lesehan stalls are still managed traditionally, simple, and unpretentious. This research is qualitative, that is research conducted by collecting data from informants (interview) and observation, also documentation. This research makes interview to the owner of tent cafes about how they serve consumers. This research works during at least two mounts. They serve consumers in a simple way and it is not professionally. So that it is important to give best service (prima service) for the consumers to increase their income. Because, in philosophy of business is known that customers or consumers do not only buy product but also the service.Entrepreneur means creating employment for our self and others, to get income for fulfilling the requirement of life.Prima service pays attention to customer as unique and interesting person, which deserves to get the best and satisfied service. Giving prima service to customer has a purpose to win competition in a business.Keywords: creativity, prima service, entrepreneur, and unemployment.